2020
DOI: 10.1177/1940161220907018
|View full text |Cite
|
Sign up to set email alerts
|

Populist Attitudes and Selective Exposure to Online News: A Cross-Country Analysis Combining Web Tracking and Surveys

Abstract: Research has shown that citizens with populist attitudes evaluate the news media more negatively, and there is also suggestive evidence that they rely less on established news sources like the legacy press. However, due to data limitations, there is still no solid evidence whether populist citizens have skewed news diets in the contemporary high-choice digital media environment. In this paper, we rely on the selective exposure framework and investigate the relationship between populist attitudes and the consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 53 publications
5
88
0
2
Order By: Relevance
“…Müller and Schulz (2019) differentiated between occasional and frequent alternative news use and found that populist attitudes linked to right-wing ideology increase the probability of reg-ular right-wing alternative news use. Similarly, Stier, Kirkizh, Froio, and Schroeder (2020) showed that people with populist attitudes consume alternative news media more frequently. This is reflected in the next hypothesis.…”
Section: Political and Populistmentioning
confidence: 99%
“…Müller and Schulz (2019) differentiated between occasional and frequent alternative news use and found that populist attitudes linked to right-wing ideology increase the probability of reg-ular right-wing alternative news use. Similarly, Stier, Kirkizh, Froio, and Schroeder (2020) showed that people with populist attitudes consume alternative news media more frequently. This is reflected in the next hypothesis.…”
Section: Political and Populistmentioning
confidence: 99%
“…In short, if perception is reality, democratic citizens may inhabit starkly different worlds, shaped in large part by the distinct information ecologies they engage with on a daily basis. And while contemporary news diets and experiences of politics may not necessarily be as fragmented and idiosyncratic as implied by the most pessimistic scenarios (as shown by Stier et al 2020 in this special issue), some of the niche news ecosystems that have developed over the past few years raise concerns for democratic governance, which this Special Issue aims to address.…”
Section: Caught Off Guardmentioning
confidence: 99%
“…Since citizens tend to choose sources that are congruent with their political preferences, and since the rise of populism has been identified as a potential challenge to liberal democracy, understanding the news diets of populist voters can shed light on the ways in which the Internet may have helped create a fertile breeding ground for populist ideas. To shed light on these issues, Stier and colleagues (2020) combine web tracking and survey data in five European democracies and the United States. They find that citizens with populist attitudes consume news from a variety of online sources and do not necessarily avoid public service media, even though many populist leaders have directly challenged and lambasted these outlets.…”
Section: Clarifying Challenges Assessing Solutions: This Special Issuementioning
confidence: 99%
“…While the study found no difference among the "digital-only" and traditional media users, it showed that people exhibiting stronger populist attitudes preferred Facebook as a source of political information, while those with lower populist attitudes preferred Twitter. Also important for our investigation is a six-country study that examines the links between populist attitudes and online news consumption (Stier et al, 2020). In line with existing research on the selective exposure framework, this study shows that populist attitudes correlate with higher reliance on hyper-partisan online outlets and lower reliance on legacy press websites, but it also shows that populist citizens do not avoid public service news, rely overwhelmingly on legacy press websites rather than hyper partisan sources, and-surprisingly perhaps-consume less tabloid news (ibid., p. 13).…”
Section: Different Media Types Different Effects?mentioning
confidence: 99%
“…Despite expanding scholarship in the area of news consumption and electoral support for anti-immigration parties, there are clearly numerous research gaps that prevent us from drawing a more comprehensive picture of this relationship-from fragmented and sometimes contradictory evidence concerning exposure to different media types, to limited crossnational comparability of the findings. The validity of existing findings can be questioned as well, as existing research is mostly-with one notable exception (Stier et al, 2020)-based on self-reported (as opposed to actual) media use and exposure to, which is known to suffer from systematic misreporting and exaggeration .…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%